Operando Reflectance Microscopy on Polycrystalline Surfaces in Thermal Catalysis, Electrocatalysis, and Corrosion - Pfaff, Sebastian (ACS Appl Mater Interfaces, 2021)
[Image: see text] We have developed a microscope with a spatial resolution of 5 μm, which can be used to image the two-dimensional surface optical reflectance (2D-SOR) of polycrystalline samples in operando conditions. Within the field of surface science, operando tools that give information about the surface structure or chemistry of a sample under realistic experimental conditions have proven to be very valuable to understand the intrinsic reaction mechanisms in thermal catalysis, electrocatalysis, and corrosion science. To study heterogeneous surfaces in situ, the experimental technique must both have spatial resolution and be able to probe through gas or electrolyte. Traditional electron-based surface science techniques are difficult to use under high gas pressure conditions or in an electrolyte due to the short mean free path of electrons. Since it uses visible light, SOR can easily be used under high gas pressure conditions and in the presence of an electrolyte. In this work, we use SOR in combination with a light microscope to gain information about the surface under realistic experimental conditions. We demonstrate this by studying the different grains of three polycrystalline samples: Pd during CO oxidation, Au in electrocatalysis, and duplex stainless steel in corrosion. Optical light-based techniques such as SOR could prove to be a good alternative or addition to more complicated techniques in improving our understanding of complex polycrystalline surfaces with operando measurements.